Insight into defect-engineered gallium oxynitride nanoparticle-based electrodes with improved electrochemical performance for supercapacitors. (1st February 2022) - Wang, Jiayu; Wu, Xuena; Lu, Xifeng; Xu, Zhen; Jiang, Haihui; Liu, Libin; Ban, Qing; Gai, Ligang
Highlights: Both cation and anion defects are introduced into gallium oxynitride (GON) nanoparticles. The GON-based electrode performance is dramatically improved via defect engineering. V Ga and V O are conducive while V N is adverse to the improved electrode performance. There is no linear relationship between defect concentration and improved performance. Abstract: Gallium oxynitride (GON) with phase resembling that of wurtzite gallium nitride (GaN) is a promising electrode material for supercapacitors. However, pristine GON nanoparticles exhibit relatively low specific capacitance, limiting their wide application in energy storage systems. In this paper, we report on dramatic increase in electrochemical performance of GON nanoparticle-based electrodes through purposefully introducing both cation and anion defects in the electrodes via controllable electrochemical etching. The textural property, band structure, and defect concentration of the electrodes can be engineered by altering the etching time. The functions of both cation and anion defects on the electrode performance have been clarified on the basis of experimental and theoretical computation results. The enhanced electrochemical performance for the etched electrodes is attributed to (i) elimination of the surface oxide layer; (2) improved specific surface area ( S BET ) and pore volume ( V pore ); and (iii) engineered cation and anion defects. It is the synergistic effect of cation and anion defects, rather than S BET and V pore, that determines the electrochemical performance of the electrodes. The GON nanoparticle-based electrodes with engineered defects have potential application in supercapacitors. Graphical abstract: Electrochemical etching on gallium oxynitride nanoparticle-based electrodes generates both cation and anion defects, in which V Ga and V O are conducive while V N is adverse to the improved electrode performance. Image, graphical abstract